2005
DOI: 10.1007/s10653-004-3479-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of cadmium and nickel from synthetic sediments by Acidithiobacillus ferrooxidans

Abstract: The microbial leaching process was evaluated for the treatment of synthetic sediments contaminated with cadmium and nickel sulfides. A series of batch leaching experiments was conducted to compare metal solubilization in sediment inoculated with Acidithiobacillus ferrooxidans -inoculated sediments to that in sterile control sediment. The rate and extent of metal solubilization were significantly higher in A. ferrooxidans -inoculated reactors than in acidified sterile reactors. The efficiency of cadmium (Cd) so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
3
4
0
Order By: Relevance
“…These results are in accordance with previous reports by Kim et al (2005), Liang et al (2010), Velgosova et al (2013), and Jadhav and Hocheng (2014a). These authors suggested that Fe(III) plays a vital role in solubilization of metals.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in accordance with previous reports by Kim et al (2005), Liang et al (2010), Velgosova et al (2013), and Jadhav and Hocheng (2014a). These authors suggested that Fe(III) plays a vital role in solubilization of metals.…”
Section: Resultssupporting
confidence: 93%
“…Fe(III) is a strong oxidizing agent. It can solubilize the metals as per following reaction (Kim et al 2005):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jadhav and Hocheng (2013) investigated silver extraction from spent silver oxide-zinc button cell battery using Acidithiobacillus ferrooxidans, and considered indirect non-contact leaching was the predominant mechanism for metal solubilization. Kim et al (2005) demonstrated indirect non-contact leaching performed better than direct leaching in bioleaching of cadmium and nickel from synthetic sediments.…”
Section: +mentioning
confidence: 94%
“…Most of the metals dissolution needed relative short time in the initial 5-10 days. It can be inferred that at the initial bioleaching the predominant mechanism responsible for the solubilization of metals from the spent Ni-Cd batteries was non-contact mechanism (acid dissolution) [21]. And the longer HRT was advantageous for the dissolution of some materials difficult to dissolve such as metallic phases.…”
Section: Metals Dissolution At Different Process Loadmentioning
confidence: 99%